Kualitas Pelayanan dan Kepuasan Pengguna Pasar Pemalang Kabupaten Pemalang - Wijayanto, Eko (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
In the midst of fierce competition in the modern market, market Pemalang still faced with the problem of inadequate infrastructure, market atmosphere is chaotic, spatial layout, diversity and quality of the goods, sales promotion, operating hours limited market, management and optimal use of selling space is not maximized. Under these conditions, this study looked at the existence of serious problems regarding the quality of services provided by market Pemalang to consumers. This study aims to determine how the service quality Pemalang market from the aspect of physical, non-physical and user satisfaction Pemalang Market. The method used in this research is descriptive research method qualitative and quantitative. The results showed that of the physical aspects of location, Pemalang Market has provided a very good service for a very strategic location and meets the safety and health aspects. In the layout of buildings and facilities, Pemalang Market is not giving good service, especially related to circulation and zoning traders as well as capacity building. By supporting infrastructure, Pemalang Market already provide pretty good service but keep their proper maintenance in order to function properly. Meanwhile, intangible services Pemalang Market is still very far from the good wishes was related to management, competency managers and traders, as well as policies related to the management of the market. While sellers and buyers are satisfied with the performance of services Pemalang Market, but felt not quite up overall.